Performance Evaluation of Three Diagnostic Methods for Soil-Transmitted Helminth Infections among Schoolchildren in Amhara Region, Northwest Ethiopia - Shegaw Belay; Getaneh Alemu; Tadesse Hailu (Journal of Tropical Medicine)
Background. Soil-transmitted helminths are parasitic nematodes found in the intestine. They are more prevalent in the tropics and subtropics, including Ethiopia. However, low-sensitive direct wet mount microscopy fails to detect soil-transmitted helminths among infected cases. Therefore, more sensitive and cost-effective diagnostic methods are urgently needed to minimize soil-transmitted helminthiasis morbidity. Objective. This study aimed to compare and evaluate the performance of diagnostic methods for soil-transmitted helminths against the “gold” standard. Methods. An institution-based cross-sectional study was conducted among 421 schoolchildren from May to July, 2022 in the Amhara Region. Study participants were selected using a systematic random sampling technique. Stool samples were processed via Kato–Katz, McMaster, and spontaneous tube sedimentation techniques. Data were entered into epi-data version 3.1 and analyzed using SPSS version 25. The sensitivity, specificity, positive predictive value, and negative predictive value were calculated against the combined result as a “gold” standard. The strength of agreement between the diagnostic methods was determined by the Kappa value. Results. The overall prevalence of soil-transmitted helminths was 32.8% (95% CI: 28.2–37.8%) using a combination of methods. The detection rates of Kato–Katz, McMaster, and spontaneous tube sedimentation were 28.5% (95% CI: 24.2–33.2%), 30% (95% CI: 25.6–34.8%), and 30.5% (95% CI: 26.1–35.3%), respectively. Sensitivity and negative predictive values were 87.1% (95% CI: 80.2–92.3%) and 95.1% (95% CI: 92.6–96.8%) for Kato–Katz; 91.7% (95% CI: 85.6–95.6%) and 96.5% (95% CI: 94.1–98.0%) for McMaster; and 93.2% (95% CI: 87.5–96.8%) and 97.1% (95% CI: 94.7–98.4%) for spontaneous tube sedimentation. Kappa values of Kato–Katz, McMaster, and spontaneous tube sedimentation for the diagnosis of soil-transmitted helminths were 0.901, 0.937, and 0.948, respectively. Conclusion. Kato–Katz, McMaster, and spontaneous tube sedimentation techniques had comparable sensitivity with almost perfect agreement for the detection of soil-transmitted helminths. Therefore, the spontaneous tube sedimentation technique can be used as an alternative diagnostic method for soil-transmitted helminth infections in endemic countries.